Imaging drusens using Spectral Domain Optical Coherence Tomography - Gella, Laxmi (Saudi J Ophthalmol, 2016)
PURPOSE: The purpose was to evaluate pathological changes of photoreceptor layer and retinal pigment epithelium in eyes with drusens using Spectral Domain Optical Coherence Tomography (SD-OCT). METHODS: Twenty-nine eyes of 29 patients with (drusens) dry age-related macular degeneration and 43 eyes of 43 controls were included in this study. All subjects underwent complete ophthalmic examination including SD-OCT. Central foveal thickness (CFT), photoreceptor layer (PRL) thickness and retinal pigment epithelial (RPE) thickness were measured and compared between the groups. P value < 0.05 was considered statistically significant. RESULTS: Best corrected visual acuity (BCVA) ranged between 20/20 and 20/200. RPE (36.10 ± 5.48 μm Vs 39.27 ± 4.30) and PRL thickness (53.93 ± 7.36 μm Vs 61.20 ± 4.50 μm) were significantly reduced in patients with drusens compared to controls. Increase in age was a significant risk factor for drusens (OR: 1.22, p < 0.001) and increased PRL thickness was a protective factor (OR: 0.720, p = 0.002). PRL thickness was significantly associated with BCVA (p = 0.019). CONCLUSION: With an increased resolution of SD-OCT, the involvement of the outer retinal layers was more clearly defined. SD-OCT may allow for the early detection of exudative changes.